Statistical index for the diagnosis of sarcopenia in physically active older women: A cross-sectional study - Jhon Fredy Ramirez Villada; Carlos Mario Arango Paternina; José Fernando Zea Castro; Annie Tibaduiza (Universidad de Antioquia, 2024)
Objective: The detection and classification of sarcopenia involves the analysis of many variables (50 to 60), which increases the time and costs required to diagnose and manage this condition. The objective of the study was to develop a synthetic statistical index to diagnose and classify sarcopenia in physically active women over 60 years old. Methodology: We conducted a cross-sectional study on 100 physically active women (64.88 ±4.4 years) on whom body composition measurements, muscle strength, and gait tests were performed. One thousand random selections of both training and test sets (80% and 20%, respectively) were made, logistic regression was fitted, and the regularization procedure (Elastic net regression) was performed. Results: the skeletal appendicular mass index (kg/m2), muscle mass (kg/m2) and SAMI (kg/m2) are highly correlated (0.93) and slow gait speed (m/sec) were the variables that contributed the most to the diagnosis of sarcopenia with a visibly high correlation, (94%). Conclusion: appendicular lean mass, gait speed, and explosive strength sufficiently describe the state of muscle and functional deterioration (sarcopenia) in physically active older women. Also, the precise identification and classification of this condition facilitates comprehensive multidisciplinary intervention, increasing the positive impact of health promotion and disease prevention programs